Analisis Prosedur Perizinan Berusaha Dalam Menjaga Kelestarian Lingkungan - Besta, Iglasias La (Universitas Sang Bumi Ruwa Jurai, 2024)
In carrying out a business licensing procedure, both individuals and business entities need to pay attention to strict regulation and supervision of their business activities. One important aspect of the business licensing procedure is the environmental impact assessment. The author is interested in discussing how business licensing procedures are implemented in an effort to preserve the environment by entrepreneurs and the government. This research uses a juridical-normative research method, while the data analysis method used is qualitative and the data collection tool used is document study. The results of this research article are that a number of efforts have been made to increase the effectiveness of the business licensing process in protecting the environment, one of which is by strengthening environmental monitoring institutions at the central and regional levels. Apart from that, the application of technology and information systems can also help speed up the business licensing process while still paying attention to environmental aspects.